Periodontally accelerated osteogenic orthodontics: Novel perio-ortho interrelationship - Sahitya Sanivarapu; Pavan Kumar Addanki; Rajababu Palaparty; Chaitanya Adurty (Journal of Indian Society of Periodontology, 2018)
Periodontally accelerated osteogenic orthodontics (PAOO) is a clinical procedure that incorporates selective corticotomy, particulate grafting, and application of optimal orthodontic forces. It reduces treatment time, increases stability of teeth, and prevents relapse of orthodontic tooth movement (OTM). The present case report highlights the technique and principles of PAOO for rapid OTM.